Novel Multidisciplinary Management of a Retropharyngeal Hematoma With Pulmonary Stenting. Issue 3 (July 2016) - Cox, Steven T.; Zimmerman, Eric; Collins, Drew; Richmond, Nicholas L.; Simoff, Michael
Abstract : Summary: Retropharyngeal hematomas (RHs) represents a rare airway obstruction that requires timely intervention to avoid a fatal outcome. Further complicating this malady, RHs of massive proportions can complicate the decision of management selection. After comprehensive literature search, there has been no mention of pulmonary stenting as an intervention for RH. The following case presentation will demonstrate the importance of multidisciplinary management of a 60-year-old presenting with a RH causing airway obstruction, with the use of a novel approach. Airway stenting is a novel, conservative approach for successfully managing patients presenting with massive RH.